“Teachers' Emotional Labor” Publications in Web of Science: A Bibliometric Analysis - Wu, Aihui; Wei, Rining (Frontiers in Psychology, 2022)
One of the indicators that symbolizes the success of an academic field is its academic publications in well-established citation indices such as Web of Science (WoS). The present paper first explored the bibliometric characteristics of publications on ‘teachers’ emotional labor’(TEL) in the Social Sciences Citation Index (SSCI) and the Arts & Humanities Citation Index (A&HCI) of WoS. Search with the term ‘teacher emotional labor’ retrieved 173 publications that included this term in their titles, abstracts or keywords in the WoS between 1900 and 2020. The bibliometric characteristics pertaining to numbers of publications, document types, research categories, research areas, authors, journals, universities and countries were reported. Then CiteSpace was utilized to visualize TEL research and to obtain insights into its research focuses and its future directions. The findings will contribute to TEL research by informing scholars in the fields of L2 research and psychology and beyond.